Structural, morphology and electrical studies of Cu-In-Se (CIS) thin films by RF magnetron sputtering machine for solar cells applications - A., Lennie; Abdullah, Huda; S., Habibi; Shaari, Abdul Halim; Lim, Kean Pah; Talib, Zainal Abidin (Persatuan Sains dan Teknologi Keadaan Pepejal Malaysia, 2010)
CuInSe2 (CIS) thin films can be described as one of the best candidate as absorber material for solar cell application. The CIS thin films have been prepared by radio frequency (RF) magnetron sputtering from compound ternary fan-shaped targets on low-temperature substrates with pure argon gas as the atmosphere. The stoichiometry of the ternary compound semiconductor quantum dots can easily be controlled by the ratios of the ternary elements and sputtering parameters. The CIS thin films were deposited onto FTO glass substrate in 40 min of deposition time. The annealed process of CIS thin film at 100°C in 30 min was done. The composition of CIS is obtained from a composite target consisted of copper disk of 99.99% purity, indium and selenium thin foil of 99.99% purities. The CIS nanoparticle thin films regularly shaped and distributed reasonably uniform in size on substrates CIS samples have been characterized by using Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). The electrical properties of the samples were measured by a standard collinear four point probe technique.